AMH in PCOS: Controlling the ovary, placenta, or brain?. (June 2020) - Moolhuijsen, Loes M.E.; Visser, Jenny A.
Abstract: Polycystic ovary syndrome (PCOS) is a very heterogeneous disease of which the exact pathophysiological mechanisms remain unknown. In PCOS, serum anti-Müllerian hormone (AMH) levels are significantly increased. AMH is a member of the transforming growth factor β family and is expressed by growing follicles in the ovaries. In PCOS, the transcriptional regulation of AMH and AMHR2 is altered, increasing and prolonging its temporal expression pattern. Moreover, the recently discovered extragonadal effects of AMH suggest that there might be a crosstalk between the ovary–placenta–brain. This review summarizes the recent findings concerning AMH and its role in the etiology of PCOS.